Variability in Resource Utilization in the Evaluation and Management of Simple Febrile Seizures Inpatients in US Children's Hospitals. Issue 1 (6th January 2023) - Saksa, Dane; Sun, Lena S.; Rodean, Jonathan; Berry, Jay; Hall, Matt; Leahy, Izabela; Ferrari, Lynne; Huang, Yolanda Y.
Abstract : Objective: To characterize resource utilization in the evaluation and treatment of hospitalized simple febrile seizure (SFS) patients in US tertiary pediatric hospitals. Methods: This is a retrospective cohort study using the Pediatric Health Information System from 2010 to 2015. Children 6 months to 5 years of age who were inpatients with a diagnosis of SFS. Children who had brain magnetic resonance imaging (MRI), electroencephalography (EEG), or received anticonvulsants were compared with those who did not have testing or anticonvulsant treatment. Hospital-level variation in the utilization rates of MRI, EEG, or treatment with anticonvulsants was also evaluated. Results: In Pediatric Health Information System-participating institutions, 8.4% (n=3640) of children presenting to the emergency department with SFS were hospitalized. Among these SFS inpatients, 57.8% (n= 2104) did not receive further evaluation with MRI/EEG or treatment with anticonvulsants. There was evidence of wide inter-hospital variation in resource utilization rates. The median (interquartile range) utilization rate was 6.2% (3.0 to 11.0%) for MRI, 28.5% (16.0 to 46.3%) for EEG and 17.1% (10.9 to 22.3%) for treatment with anticonvulsants. Conclusion: No specific hospital-level factors were identified that contributed to the variation in resource utilization in the evaluation and management of hospitalized SFS patients.